Is Sustainability Reporting Really About Reporting Sustainability? - Ardiana, Putu Agus (Jurnal Ilmiah Akuntansi dan Bisnis, 2023)
Global Reporting Initiative (GRI) introduces a sustainability reporting framework known as GRI standards. Despite its popularity, the GRI standards receive criticism for having covered a broad range of topics but seemingly irrelevant to stakeholders. The objective of this paper is to examine whether the GRI standards truly provide guidelines for reporting what sustainability ought to be reported. This paper uses the thematic analysis to examine whether themes that appear in the GRI standards are in line with Ben-Eli’s (2018) five domains of sustainability (the material, economic, life, social, and spiritual domains). This paper finds that the GRI’s sustainability standards lack the spiritual domain. The spiritual dimension is fundamental to sustainability reporting quality and the coherence of the whole reporting process. The main contribution of this paper is in the form of providing insights into the need to report sustainability as it is, with its root in the ecology field. Keywords: sustainability reporting, sustainability domains, reporting framework, thematic analysis